Efficacy and toxicity of carboplatin and cytarabine chemotherapy for dogs with relapsed or refractory lymphoma (2000–2013). (14th October 2015) - Gillem, J.; Giuffrida, M.; Krick, E.
Abstract: Medical records of 22 dogs treated with carboplatin ( n  = 8) or carboplatin and cytarabine ( n  = 14) chemotherapy for relapsed or refractory lymphoma between 2000 and 2013 were retrospectively reviewed. The clinical response rate was 18.2% (4/22). Median time to progression was 18 days (56 for responders; 12 for non‐responders, P  = 0.0006). Median overall survival time was 28 days (109 for responders; 21 for non‐responders, P  = 0.0007). Thrombocytopenia and neutropenia occurred in 84.2% (16/19) and 52.6% (10/19), respectively. Grade IV thrombocytopenia and neutropenia occurred in 56.3% (9/16) and 60.0% (6/10), respectively. Dogs that received both drugs were more likely to become neutropenic ( P  = 0.022) or thrombocytopenic ( P  = 0.001) than dogs receiving carboplatin alone. All responders received both drugs giving a 28.6% (4/14) response rate for the combination. Although some dogs responded to the combination, toxicity was high and the responses were not durable. With adequate supportive care, this protocol may be an acceptable rescue option for some dogs.